Mediating effect of attitude on competitive sports participation and academic achievement of university students in the Eastern Region of Saudi Arabia - Al-Ahmed, Mustafa Issa A. (2017)
The main objective of this current study is to investigate how the attitudes of the undergraduate student-athletes mediate the relationship between the participation in competitive sports (PCS) and the academic achievement (AA). The two attitudes being studied are namely the attitude towards academic achievements (ATAA) and the attitude towards participation in competitive sports (ATPCS). Using questionnaire as research instrument, a total of three hundred undergraduate student-athletes from six academic institutions in the Eastern Region of Saudi Arabia were asked to respond to the scale of Attitudes toward Physical Activity (ATPA) to obtain data on ATPCS, the Survey of Study Habits and Attitudes (SSHA) to obtain data on ATAA, and directly enquire the participants about their point average of academic grade (GPA) and the frequency of their competitive sports participation, to obtain data on AA and PCS. The results indicated that PCS significantly predicts the AA [F(1, 298)=272.27, p<.01], whereas ATPCS and ATAA significantly mediate the influence of PCS on AA [Beta value changed from .691 to .695 for ATPCS and from .691 to .520 for ATAA]. The results indicated that the more active an individual to participate in competitive sports, the better his academic performance; however, when his attitude towards participation in competitive sports and his attitude towards academic achievement are more positive, the influence of his participation in competitive sports on academic achievement become stronger. These results could be attributed to the regulation from Saudi Universities Sports Federation (SUSF) that only undergraduate student-athletes who achieve certain academic scores (GPA) can participate in competitive sports. The findings showed that the interrelationship among variables occur when a proper regulation is enforced in order to achieve better condition (student-athletes with high achievements both in sports and academics), because the interrelationship among the variables in this current study might not occur without the regulation.